Hyperstable EGF-like bleogen derived from cactus accelerates corneal healing in rats - Loo, Shining; Kam, Antony; Tam, James P. (Frontiers in Pharmacology, 2022)
Corneal scarring reduces corneal transparency, compromises vision, and is a major cause of vision loss worldwide. Epidermal growth factor (EGF), which is the prototypic member of the EGF receptor (EGFR) agonists, is present in tears to provide repair and regeneration. Recently, we discovered bleogen pB1 in the cactus plant Pereskia bleo and showed that it is a non-canonical and hyperstable EGFR agonist with EGF-like wound healing properties for diabetic rats. Here, we apply bleogen pB1 to accelerate corneal wound healing in rats. To assess the corneal healing effects of bleogen pB1, we induced an acute alkali burn to the right eye of male Wistar rats. After five consecutive ophthalmic applications, fluorescein staining and opacity scores of the bleogen pB1-treated, and the positive control EGF-treated groups improved significantly compared to the saline control group. Immunohistochemical analyses revealed that infiltrated CD68+ macrophages and the expression of the myofibroblast marker alpha smooth muscle actin (α-SMA) were significantly decreased in the bleogen pB1- and the EGF-treated groups. By employing a differential gene expression analysis of bleogen pB1- and EGF-treated keratinocytes through RNA-seq, we demonstrated that bleogen pB1 or EGF treatments can affect the expression of genes associated with inflammatory responses and extracellular matrix remodeling. Taken together, our results indicate that the plant-derived EGFR agonist bleogen pB1 can produce similar effects to those of EGF in accelerating corneal wound healing as well as in reducing persistent inflammation and myofibroblast accumulation in the cornea.